Prevalence of Protozoa Infections in Domestic Cats - Ivan Taufiq Nugraha; Tetty Barunawati Siagian (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
This study aims to determine the prevalence of helminthiasis infection in domestic cats that live freely in the IPB Gunung Gede campus. This study used 15 samples of stray cat feces that live in the IPB Gunung Gede Campus. The collected fecal samples were then examined qualitatively by native and flotation methods. The results showed that 4 out of 15 feral cats were positively infected with protozoa with a prevalence of 26.6% on flotation examination, whereas on native examination, the results were negative. The positive result was indicated by the discovery of oocysts during flotation examination. The positive feral cat was found with watery diarrhea condition and his hair looks dull. Protozoal infections are more common in feral cats than in domestic cats. Protozoal infections can cause disturbances in the digestive tract in the form of diarrhea and are zoonotic.